Association of MC4R, RYR1 and PRKAG3 single nucleotide polymorphisms with body weight in crossbred piglets - PANDA, SNEHASMITA; GAUR, G K; SAHOO, N R; SAINI, B L (The Indian Journal of Animal Sciences, 2019)
An attempt was made to study the association of MC4R, RYR1 and PRKAG3 SNPs with body weight from birth to 8 weeks in 238 crossbred pigs. The lower value of PIC, observed heterozygosity, expected heterozygosity and number of effective alleles for RYR1 and PRKAG3 SNP revealed that population under investigation was of low diversity maintaining a single allele. These values were intermediate for MC4R SNP representing that forces had been operated to maintain both alleles in the population. Chi square value was significant for MC4R showing significant departure from the Hardy–Weinberg equilibrium. Effect of all SNPs was non-significant on body weight at all ages. Though non-significant, GG genotype of MC4R SNP, NN genotype of RYR1 SNP and QR genotype of PRKAG3 SNP had better weight at 6 and 8 week as compared to their contemporary genotypes, i.e. AG and AA genotype of MC4R SNP, Nn genotype of RYR1 SNP and RR genotype of PRKAG3 SNP. Fourth parity piglets had higher body weight at all ages as compared to those born in other parities. Piglets born from March to June had a higher growth at most of the weeks as compared to rest of the seasons. Piglets born in 2016 had higher growth at most of the weeks. The effect of sex was non-significant on body weight at all ages.